Effect of Kinetin and 2,4-D Plant Growth Regulators on In Vitro Subculture Growth of Dendrobium stockelbuschii - Talitha, Okky; Yamauchi, Kosei; Setyawati, Andriyana; Iqbal, Muhammad; Saskya, Nanda (Agrosains : Jurnal Penelitian Agronomi, 2025)
Dendrobium orchids are a popular genus due to their adaptability and wide variation in flower shapes and colors. Conventional propagation methods face challenges in producing large quantities of high-quality seedlings. This study aimed to produce superior-quality seedlings through tissue culture techniques using ½ Murashige and Skoog (MS) medium supplemented with kinetin and 2,4-D to enhance growth. The research was conducted at the Plant Physiology and Biotechnology Laboratory, Sebelas Maret University, from February to July 2024. The experimental design used was a completely randomized design (CRD) with two factors. The first factor was kinetin concentration (0, 0.5, 1, 1.5, 2 ppm), and the second factor was 2,4-D concentration (0, 0.5, 1, 1.5, 2 ppm). A total of 25 treatment combinations were tested, each replicated three times, resulting in 75 experimental units. Observed parameters included the number of roots, plant height, number of shoots, and root length. Data were analyzed using analysis of variance (ANOVA) at a 5% significance level, followed by Duncan’s Multiple Range Test (DMRT) for mean separation. The results showed that kinetin had a significant effect on the number of roots and plant height, while 2,4-D significantly affected root length. No significant interaction was observed between the two factors.